The inadequacy of classical regulatory approaches in a complex environment - Mirko Pečarič (DANUBE: Law, Economics and Social Issues Review, 2020)
The interactions, interdependence, dynamism, diversity, emergency and other elements of complexity should be embedded in legal rules to cope with the complex environment. If it is obvious that the latter is hard to manage with the classical forms of legal rules, this common-sense is tricking us into an insistence on such rules. The complex environment and the people are complex adaptive systems, and such should be also legal rules when applied in such an environment. Public systems should systemically address the environment because the latter is per se blind to rules. The aim of this paper is to give directions towards the use of complex adaptive rules with the enumeration of elements of complexity. Based on the elaborated and included elements of complexity the paper finds that collective decision-making, here named as synomy, presents the appropriate shift from experts to the people and database oracles. The possibility to store and process a large amount of data (with the better statistical prediction) gives collective wisdom preference over the people as individuals, over experts and the classical legal approaches. Based on this the paper presents different rules that are accustomed to different environments.
Keywords: 330; Complexity; Practical and Collective Wisdom; Public Decision-making; IT Democracy; Synomy